2007
DOI: 10.1128/aac.00880-06
|View full text |Cite
|
Sign up to set email alerts
|

Caspofungin in Combination with Amphotericin B against Candida parapsilosis

Abstract: Candida parapsilosis has emerged as an important nosocomial pathogen. In the present study, a checkerboard broth microdilution method was performed to investigate the in vitro activities of caspofungin (CAS) in combination with amphotericin B (AMB) against three clinical isolates of C. parapsilosis. Although there was a significant reduction of the MIC of one or both drugs used in combination, an indifferent interaction (fractional inhibitory concentration index greater than 0.50 and less than or equal to 4.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…With regard to echinocandins, most authors found no antagonism between micafungin and azoles or AMB (4,17,32). Barchiesi et al did not find advantages in associating caspofungin and the polyene, with the exception of C. parapsilosis, but the study in- cluded a much more limited number of strains (2). In some Candida strains, echinocandins are highly active, and so the fungicidal activity may be difficult to improve after combination (17).…”
Section: Discussionmentioning
confidence: 91%
“…With regard to echinocandins, most authors found no antagonism between micafungin and azoles or AMB (4,17,32). Barchiesi et al did not find advantages in associating caspofungin and the polyene, with the exception of C. parapsilosis, but the study in- cluded a much more limited number of strains (2). In some Candida strains, echinocandins are highly active, and so the fungicidal activity may be difficult to improve after combination (17).…”
Section: Discussionmentioning
confidence: 91%
“…Caspofungin has potent antifungal activities and has been shown to be as effective as, and less toxic than, amphotericin B in the treatment of invasive candidiasis caused by C. albicans, C. parapsilosis, C. tropicalis, C. glabrata, C. krusei, C. guilliermodii, C. lipolytica, and C. rugosa (180,262). However, caspofungin MICs for C. parapsilosis are higher than those for other Candida species, with average MIC 50 and MIC 90 values ranging between 0.85 to 2 g/ml and 2 to 2.33 g/ml, respectively (17,18,88,146,202). Although the basis for this resistance is not clearly understood, structural differences in the components of the cell wall, a reduced affinity for the glucan synthase protein complex, or a difference in its regulatory network may be responsible (17).…”
Section: Antimicrobial Susceptibilitymentioning
confidence: 88%
“…For C. parapsilosis, caspofungin in combination with amphotericin B can significantly improve potency in vitro and in a murine infection model (18). Clinical data detailing the effectiveness of combination therapy are rare, although a few case reports have been published.…”
Section: Antimicrobial Susceptibilitymentioning
confidence: 99%
“…are observed, whereas antagonism is rarely detected (2,3). However, the results of the Etest-1 study indicate that this method could be an acceptable alternative to time-kill studies with antifungal agents.…”
mentioning
confidence: 89%
“…The positive interaction between an echinocandin compound and a polyene can be explained by the fact that both drug families possess unique mechanisms of action. It can be postulated that the candins, which inhibit cell wall synthesis, may enhance the activity of AMB by increasing the rate or degree of their access to the cell membrane (3).…”
mentioning
confidence: 99%